Correlation of Haemoglobin level and Urine Albumin in relation to Glycated Haemoglobin in Type 2 Diabetes - Sulochana, Sonti; Viswanath, Ashok; A.N, Siddharth Gautam; Srinivasan, Chitra (Annals of Pathology and Laboratory Medicine, 2018)
Aim and Objective : The Aim and objective of the present study is to correlate haemoglobin , urine albumin with glycated haemoglobin also called as HbA1c testing. Settings and Design : This study was conducted on 100 Diabetic patients without hypertension ,coronary artery disease & pregnancy. Methods and Material : Blood samples of diabetic subjects were collected and analyzed for Glycated haemoglobin using Glucose oxidase method and haemoglobin using automated analyzer sysmex XN 1000, Urine albumin measured with URODIP 10A Reagent strips . The data was analyzed by descriptive analysis. Result And Conclusion : Result shows that Haemoglobin were significantly reduced in diabetic patients with high glycated haemoglobin and presence of urine albumin which is highly increased in diabetic patients with high glycated haemoglobin . DOI:10.21276/APALM.1626